The Possible Correlation between the Patient's Immune Tolerance Level During Cesaerean Section and the Incidence of Subsequent Emergency Peripartum Hysterectomy - Lukasz Wicherek; Krystna Galazka (Clinical and Developmental Immunology)
Introduction. Cesarean section is an independent risk factor for peripartum hysterectomy. As a method of delivery, cesarean section may interfere with a number of molecular changes that occur at the maternal-fetal interface during the course of labor. Methods. The level of CD3, CD56, CD25, and CD69 antigen immunoreactivity was assessed by immunohistochemistry in 26 decidual tissue samples. The tissue samples were obtained from 18 women who underwent cesarean sections at term and from 8 women who underwent cesarean hysterectomies. Results. An increase in the activity and infiltration of immune cells in the decidua sampled during the spontaneous beginning of labor was observed. The further progression of labor was accompanied by a decrease in the number and activity of immune cells. The number of CD56+ and CD3+ cells in the decidua was statistically significantly lower in patients who had undergone cesarean hysterectomies than in those who had had cesarean sections at term. Conclusion. Abnormal immune response during labor may increase the risk for peripartum hysterectomy.